"Fast tracking" patients with a proximal femoral fracture. Issue 2 (March 1996) - Ryan, J; Ghani, M; Staniforth, P; Bryant, G; Edwards, S
Abstract : OBJECTIVE–To assess the management of elderly patients presenting to the accident and emergency (A&E) department with a proximal femoral fracture. METHODS–A retrospective audit carried out on 30 patients with proximal femoral fracture showed an unacceptably long waiting time in the A&E department. A new "fast track" system for managing these patients, involving the use of a flow chart for expediting admission, was devised. A prospective study of 100 patients > 60 years of age with proximal femoral fracture admitted by fast track system was then carried out. RESULTS–Implementation of the fast track system resulted in earlier admission to the ward (median time to admission 2.5 h v 4.5 h in the retrospective audit, P < 0.001). Eighteen patients were not admitted by fast track during the study period, in some cases because of inconclusive diagnosis or because there was no identifiable orthopaedic bed; mean admission time for this group was 4 h 8 min. CONCLUSIONS–The fast track system was of benefit to all involved, including the patient, A&E staff, ward staff, and orthopaedic personnel.